2019
DOI: 10.1093/jcag/gwz026
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Patient Education Prior to Colonoscopy: Prospective, Observational Study of a Single Center’s Implementation, with Objective Assessment of Bowel Preparation Quality and Patient Satisfaction

Abstract: Background Nonpharmacologic factors, including patient education, affect bowel preparation for colonoscopy. Optimal cleansing increases quality and reduces repeat procedures. This study prospectively analyzes use of an individualized online patient education module in place of traditional patient education. Aims To determine the effectiveness of online education for patients, measured by the proportion achieving sufficient bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Conclusions Optional SDBP is inferior to mandatory SDBP in providing adequate bowel preparation quality for early morning colonoscopies (8:00 AM-10:30 AM), and probably inferior for late morning colonoscopies (10:30 AM-12:00 PM). couraged to visit an informative online platform (https://mycolonoscopy.ca), which provides validated patient-education materials focused on SDBP [16]. Patients were aware of the bowel preparation instructions, but the endoscopists were unaware of the bowel preparation instructions that had been provided to the patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conclusions Optional SDBP is inferior to mandatory SDBP in providing adequate bowel preparation quality for early morning colonoscopies (8:00 AM-10:30 AM), and probably inferior for late morning colonoscopies (10:30 AM-12:00 PM). couraged to visit an informative online platform (https://mycolonoscopy.ca), which provides validated patient-education materials focused on SDBP [16]. Patients were aware of the bowel preparation instructions, but the endoscopists were unaware of the bowel preparation instructions that had been provided to the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Both SDBP groups (mandatory and optional) received standardized information regarding pre-procedure diet, medication use, and the sedatives and colonoscopy. Both groups were encouraged to visit an informative online platform (https://mycolonoscopy.ca), which provides validated patient-education materials focused on SDBP [16]. Patients were aware of the bowel preparation instructions, but the endoscopists were unaware of the bowel preparation instructions that had been provided to the patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other medical specialties have examined having patient education modules and shared patient decision aids. These studies have shown that providing procedure-specific patient education decreases the length of time patients spend in the clinic room during their consultation appointment and increases patient satisfaction rates (Trasolini et al, 2020; Ubbink et al, 2016).…”
Section: Problem Statementmentioning
confidence: 99%
“…Furthermore, patient acceptance is improved by all educational methods, including oral and written education [3], face-to-face education, and media-based education [10]. However, new methods such as utilizing technology, media [1], web applications [11], 3D online programs [12], and mobile applications [13,14] may increase patient acceptance to a greater extent, necessitating additional research on their efficacy [1]. For example, media use can make reinforced education (RE) more effective from admission until the colonoscopy day [15].…”
Section: Introductionmentioning
confidence: 99%